COVID Stress, socioeconomic deprivation, and intimate partner aggression during the COVID-19 pandemic - Julia F. Hammett; Miklós B. Halmos; Dominic J. Parrott; Cynthia A. Stappenbeck (BMC, 2022)
Abstract Background Intimate partner aggression (IPA) is a prevalent public health concern that is associated with multiple negative consequences. Rates of IPA in the U.S. have increased since the onset of the Coronavirus Disease 2019 (COVID-19) pandemic, likely due to stress associated with the pandemic. Socioeconomic deprivation is associated with COVID-19 outcomes as well as IPA. However, whether socioeconomic deprivation interacts with COVID-19 stress in predicting IPA remains unclear. Methods Using a sample of 510 individuals recruited via Qualtrics Research Services in April 2020, the present study tested whether socioeconomic deprivation moderates the association between COVID-19 stress and IPA perpetration and victimization. Participants completed a questionnaire battery that included measures of COVID-19 stressors and physical and psychological IPA perpetration and victimization. In addition, participants reported their residential zip codes, which were subsequently matched with scores on the Social Deprivation Index, a composite measure of seven demographic variables from the 5-year American Community Survey. Results Sequential generalized linear models in Mplus Version 8.7 showed that the effects of COVID-19 stress on physical IPA perpetration and psychological IPA victimization can be best understood through its interactive effects with socioeconomic deprivation. Higher COVID-19 stress was associated with higher levels of physical IPA perpetration and psychological IPA victimization when socioeconomic deprivation was low but not when socioeconomic deprivation was high. Importantly, however, overall rates of IPA were higher among individuals with higher socioeconomic deprivation than among individuals with lower socioeconomic deprivation, regardless of the amount of COVID-19 stress they experienced. Conclusions The present analyses implicate COVID-19 stress as a critical correlate of IPA and show that the association between this stress and physical IPA perpetration and psychological IPA victimization may be particularly salient among individuals who live in areas of lower socioeconomic deprivation. Furthermore, our results clearly pinpoint the detrimental effects of socioeconomic deprivation more broadly, showing that individuals who live in more deprived areas tend to have high levels of IPA regardless of their level of COVID-19 stress. These findings call for public health policies at the community and societal level that target not only COVID-related stress but also the impacts of socioeconomic inequality.